2012
DOI: 10.1007/s12185-012-1057-2
|View full text |Cite
|
Sign up to set email alerts
|

Drug interaction between voriconazole and tacrolimus and its association with the bioavailability of oral voriconazole in recipients of allogeneic hematopoietic stem cell transplantation

Abstract: In a previous study, we noted wide inter-individual variability in drug interactions between voriconazole and tacrolimus, but that analysis did not take into account the routes of administration. In the present study, we analyzed interactions between these two drugs when both agents were administered orally after allogeneic hematopoietic stem cell transplantation (HSCT); the effect of plasma voriconazole levels on the magnitude of the drug interaction was also examined. Twenty-five allogeneic HSCT recipients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 24 publications
7
22
1
Order By: Relevance
“…The proportional increase in Tac C/D (DC/D) resulting from azole co-therapy varied widely (almost 20-fold) between patients, in line with what has been previously observed in allogeneic hematopoietic stem cell transplantation (33). The proportional increase in Tac C/D (DC/D) resulting from azole co-therapy varied widely (almost 20-fold) between patients, in line with what has been previously observed in allogeneic hematopoietic stem cell transplantation (33).…”
Section: Resultssupporting
confidence: 82%
“…The proportional increase in Tac C/D (DC/D) resulting from azole co-therapy varied widely (almost 20-fold) between patients, in line with what has been previously observed in allogeneic hematopoietic stem cell transplantation (33). The proportional increase in Tac C/D (DC/D) resulting from azole co-therapy varied widely (almost 20-fold) between patients, in line with what has been previously observed in allogeneic hematopoietic stem cell transplantation (33).…”
Section: Resultssupporting
confidence: 82%
“…Metabolic interactions between tacrolimus and azole antifungal drugs are well known. It has been reported that FLCZ and VRCZ elevate blood tacrolimus levels . Our data regarding ( C iv / D iv )/( C po / D po ) ratios indicated that VRCZ increased blood tacrolimus concentrations more remarkably than FLCZ after conversion from intravenous to oral administration of tacrolimus.…”
Section: Discussionsupporting
confidence: 48%
“…Azole antifungal drugs are frequently used during the administration of tacrolimus to prevent fungal infections after HSCT. Azole antifungal drugs inhibit CYP3A activity and therefore increase the blood level of tacrolimus . In addition, the degree of CYP3A inhibition is known to vary among azole antifungal drugs .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…3 Although individual differences in drug response may vary because of age, sex, and disease, 4 the wide range of variability in TAC PK in HSCT recipients is often explained by polymorphisms in genes encoding metabolizing enzymes and drug interaction via metabolizing enzymes. [5][6][7] However, interindividual variability of blood TAC concentration during the early stages of HSCT is as of yet still difficult to predict.…”
Section: Introductionmentioning
confidence: 99%